Four Thrombotic Events Over 5 Years, Two Pulmonary Emboli and Two Deep Venous Thrombosis, When Testosterone-HCG Therapy Was Continued Despite Concurrent Anticoagulation in a 55-Year-Old Man With Lupus Anticoagulant - Charles J. Glueck MD; Kevin Lee MD; Marloe Prince MD; Vybhav Jetty MD; Parth Shah MD; Ping Wang PhD (SAGE Publishing, 2016)
Background: When exogenous testosterone or treatments to elevate testosterone (human chorionic gonadotropin [HCG] or Clomid) are prescribed for men who have antecedent thrombophilia, deep venous thrombosis and pulmonary embolism often occur and may recur despite adequate anticoagulation if testosterone therapy is continued. Case Presentation: A 55-year-old white male was referred to us because of 4 thrombotic events, 3 despite adequate anticoagulation over a 5-year period. We assessed interactions between thrombophilia, exogenous testosterone therapy, and recurrent thrombosis. In 2009, despite low-normal serum testosterone 334 ng/dL (lower normal limit [LNL] 300 ng/dL), he was given testosterone (TT) cypionate (50 mg/week) and human chorionic gonadotropin (HCG; 500 units/week) for presumed hypogonadism. Ten months later, with supranormal serum T (1385 ng/dL, upper normal limit [UNL] 827 ng/dL) and estradiol (E2) 45 pg/mL (UNL 41 pg/mL), he had a pulmonary embolus (PE) and was then anticoagulated for 2 years (enoxaparin, then warfarin). Four years later, on TT-HCG, he had his first deep venous thrombosis (DVT). TT was stopped and HCG continued; he was anticoagulated (enoxaparin, then warfarin, then apixaban, then fondaparinux). One year after his first DVT, on HCG, still on fondaparinux, he had a second DVT (5/315), was anticoagulated (enoxaparin + warfarin), with a Greenfield filter placed, but 8 days later had a second PE. Thrombophilia testing revealed the lupus anticoagulant. After stopping HCG, and maintained on warfarin, he has been free of further DVT-PE for 9 months. Conclusion: When DVT-PE occur on TT or HCG, in the presence of thrombophilia, TT-HCG should be stopped, lest DVT-PE reoccur despite concurrent anticoagulation.